Surgical Management of Endolymphatic Sac Tumors - Friedman, Rick A.; Hoa, Michael; Brackmann, Derald E. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To review the cumulative experience of surgical management of endolymphatic sac tumors (ELSTs) in the literature. To review the experience with ELST management at a tertiary referral-based otology-neurotology practice and present our approach to management.Study Design Retrospective patient review at a referral-based otology-neurotology practice.Methods A review of all available records from the House Clinic of patients with ELSTs was performed. Presentation, diagnostic workup, microsurgical approach, and outcomes were reviewed. Literature review using MEDLINE of studies reporting surgical outcomes of patients with ELSTs was also performed.Results Retrospective chart review revealed 18 patients with ELSTs who underwent surgical management. Grouping of these patients provides surgical outcomes on the largest group of mostly non–von Hippel-Lindau patients with ELSTs in the literature. Patients most commonly presented with sensorineural hearing loss, tinnitus, and dizziness. A majority of patients presented with large tumors exhibiting significant destruction of surrounding structures including the cochlea, vestibule, and internal auditory canal. Patients underwent microsurgical resection with the intent of complete resection.Conclusions Although the extensive nature of ELSTs at time of diagnosis often precludes hearing preservation, complete microsurgical resection can be achieved safely with preservation of facial function in the majority of cases.
Keywords: endolymphatic sac tumors; facial nerve function; hearing preservation